Carbapenemase-producing Enterobacteriaceae in a Portuguese hospital - a five-year retrospective study - Gorgulho, AM (2020)
Our hospital experienced an outbreak of OXA-48-producing Enterobacteriaceae, triggering this study. We aimed to describe the population with carbapenemase-producing Enterobacteriaceae (CPE) in our hospital from 2014 to 2018, the phenotypic and genotypic characteristics of isolates, and strategies to stop the outbreak.